A Facile Method to Synthesize Co3O4 Catalyst for Efficient Chlorobenzene Combustion. Issue 17 (3rd May 2022) - Li, Yan; Chen, Jing; Hu, Ziying; Lv, Xue‐Long; Jia, Hongpeng
Abstract: Preparation methods are essential for the synthesis of materials with diverse structures, which may lead to the different physicochemical properties. The activities of catalysts for volatile organic compounds (VOCs) combustion can be improved by optimizing the preparation methods. In this paper, a novel ammonium bicarbonate pyrolysis method is successfully applied to prepare Co3 O4 catalyst (Co3 O4 ‐A), which is not only facile in preparation, but also superior to the Co3 O4 catalysts prepared by the hydrothermal, sol‐gel, MOFs pyrolysis and carbonate pyrolysis method in the performance of chlorobenzene catalytic oxidation with 90 % conversion and mineralization temperature at 310 and 325 °C, respectively (1000 ppm CB, Air, WHSV=60, 000 mL ⋅ g −1  ⋅ h −1 ). Furthermore, Co3 O4 ‐A catalyst can maintain high catalytic activity for a long time, and has high tolerance to water vapor, which indicates Co3 O4 ‐A catalyst has a good potential application value in catalytic combustion of chlorobenzene. Abstract : Co3 O4 nanocrystal catalysts were synthesized by five different methods and their catalytic activates for chlorobenzene combustion were studied. The Co3 O4 ‐A catalyst obtained by ammonium bicarbonate pyrolysis method is not only facile in preparation, but also superior to the Co3 O4 catalysts prepared by the other methods (hydrothermal, sol‐gel, MOFs pyrolysis and carbonate pyrolysis) in the performance of catalytic oxidation of chlorobenzene with T90 of 310 °C.